2017
DOI: 10.1074/jbc.m117.814178
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial DnaB helicase interacts with the excluded strand to regulate unwinding

Abstract: Replicative hexameric helicases are thought to unwind duplex DNA by steric exclusion (SE) where one DNA strand is encircled by the hexamer and the other is excluded from the central channel. However, interactions with the excluded strand on the exterior surface of hexameric helicases have also been shown to be important for DNA unwinding, giving rise to the steric exclusion and wrapping (SEW) model. For example, the archaeal minichromosome maintenance (MCM) helicase has been shown to unwind DNA via a SEW mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 47 publications
1
29
2
Order By: Relevance
“…Control of DNA unwinding by replicative helicases through their interaction with the excluded strand has been demonstrated in different organisms. Although wrapping of the displaced strand around an archaeal MCM was proposed to increase its helicase activity 28 , interaction of DnaB with the displaced strand through its exterior surface adversely affects DNA unwinding 29 . While it is not clear whether CMG makes contacts with the lagging-strand template via specific residues on its outer surface, the presence of the excluded strand is important for unwinding of dsDNA by CMG.…”
Section: Introductionmentioning
confidence: 99%
“…Control of DNA unwinding by replicative helicases through their interaction with the excluded strand has been demonstrated in different organisms. Although wrapping of the displaced strand around an archaeal MCM was proposed to increase its helicase activity 28 , interaction of DnaB with the displaced strand through its exterior surface adversely affects DNA unwinding 29 . While it is not clear whether CMG makes contacts with the lagging-strand template via specific residues on its outer surface, the presence of the excluded strand is important for unwinding of dsDNA by CMG.…”
Section: Introductionmentioning
confidence: 99%
“…While one possible reason for the observed inhibition is the partial entrapment of the displaced strand (hence the parental duplex) in the helicase central pore, the other consideration is the interaction of the displaced strand with the outer surface of CMG. If a physical contact between the exterior of CMG and the laggingstrand template adversely affects helicase activity, as suggested for DnaB (Carney et al, 2017), hybridization of a complementary oligonucleotide or binding of RPA to the lagging-strand arm of a fork substrate may stimulate DNA unwinding by disrupting this interaction. To determine whether the inhibition of CMG helicase activity stems from its interaction with the displaced strand through the helicase exterior residues or interior channel, we introduced a biotinstreptavidin complex on the lagging-strand arm of a fork substrate.…”
Section: Streptavidin Binding To the Excluded Strand Is Sufficient Tomentioning
confidence: 99%
“…Control of DNA unwinding by replicative helicases through their interaction with the excluded strand has been demonstrated in different organisms. For example, while wrapping of the displaced strand around an archaeal MCM was proposed to increase its helicase activity (Graham et al, 2011), interaction of DnaB with the displaced strand through its exterior surface adversely affects DNA unwinding (Carney et al, 2017). Although, it is not clear whether CMG makes contacts with the lagging-strand template via specific residues on its outer surface, the presence of the excluded strand is important for unwinding of dsDNA by CMG.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the eukaryotic replicative DNA helicase named MCM2-7 is a member of Superfamily 6. In the process of unwinding DNA, independent biochemical studies support the model that DnaB is bound at the replication fork to one of the two parental DNA strands [ 145 , 146 , 147 ]. Cryoelectron microscopy of E. coli DnaB [ 148 , 149 ], and X-ray crystallography of Geobacillus kaustophilus , Geobacillus stearothermophilus and Bacillus subtilis DnaB showed that the native structure of DnaB is a hexamer of identical subunits assembled as a toroid [ 81 , 150 , 151 ].…”
Section: Dnabmentioning
confidence: 99%
“…Evidence indicates that DnaB and its homologues in other organisms translocate in the 5’-to-3’ direction on the single-stranded DNA to which they are bound [ 157 , 159 , 160 , 161 ]. Like other DNA helicases that are toroids [ 140 , 141 , 162 , 163 , 164 ], this DNA strand passes through the central cavity of DnaB, apparently interacting with specific residues that line the cavity during movement while the other parental DNA strand is excluded [ 146 , 147 ].…”
Section: Dnabmentioning
confidence: 99%